Kesuburan dan Hasil Jagung di Kemiringan Lahan berbeda di Kabupaten Boalemo - Bambang mamangkay; Novri Youla Kandowangko; Abubakar Sidik Katili (Jurnal Ilmu Pertanian Indonesia, 2024)
This study aims to describe the status of soil fertility and corn yield on different slopes of agricultural land in UPT SP3 Saritani Village, Boalemo Regency. The study used survey methods at 3 land slope locations (20--30%, 30–40%, and 50–60%), determined purposively. Soil samples and maize yields were analyzed quantitatively and descriptively. Corn yields were collected and compared over 3 harvesting seasons based on the parameters of agronomic components. Soil fertility was analyzed at BSIP PALMA Manado laboratory, with parameters including macronutrient components. An essential finding of this study is that there is a difference in corn yield and nutrients on the sloping lands. The fertility status of farmers' land on the average sloped land of the three stations is very low levels of nitrogen and carbon nutrients and high levels of phosphate and potassium. The agronomic components of Stations 1 and 2 were relatively similar compared to the yield of components at Station 3. In the 3 harvest seasons, Station 1's yield decreased every season; from Station 2 it also decreased, but only at the time of the third harvest, although it was insignificant. The yield from Station 3, the steepest field, decreased significantly. Keywords: bisi 18 hybrida, maize, sloping land, soil fertility